Comparative Analysis of Soil Protozoa and some Physio-chemical parameters of Effluent-Inundated Soil and Unaffected Agricultural Soils of Chhattisgarh - Ewraj Janghel; Sanju Sinha (The Bioscan, 2025)
Soil serves as the primary edaphic component of the Earth, providing a habitat for plants and various soil microorganisms such as fungi, bacteria, and protozoa. Although protozoa constitute only a small portion of the microfauna in terms of biomass, their functional importance is significantly greater. The number and variety of protozoa may be influenced by the quality of soil. The present study aimed to compare the diversity of soil protozoa between agricultural field irrigated with natural water as well as tube-well water and agricultural field irrigated with Bhilai Steel Plant effluent in Durg District. Soil samples were collected from two sites: a rice -cultivated field in Kotni village (Site -1) and a Bhilai Steel Plant effluent-inundated rice cultivated field near Sirsa village (Site -2). Physico-chemical parameters and protozoan diversity were analyzed using standard methods. Site -2 exhibited higher protozoan diversity with 23 species in comparison to site -1 with 16 species. Quantitative analyses were conducted to determine the density, percentage frequency and abundance, along with the importance value index (IVI). The Sorenson index was applied to evaluate the similarity of the protozoan species across both study sites. The Simpson and Shannon-Weiner indices were used to evaluate the diversity of the protozoan communities. This study highlighted the potential use of protozoan communities as bioindicators of industrial pollution and soil health. These findings contribute to the understanding of the impact of industrial effluents on soil ecosystems and may contribute a significance role in future environmental monitoring and management strategies.